PENYULUHAN LITERASI KEUANGAN UNTUK MENCAPAI FINANCIAL FREEDOM BAGI GEN-Z - Widhiastuti, Rosalia Nansih; Harianti, Ati; Suryowati, Budi; Suzuda, Fanny (Institut Teknologi dan Bisnis Swadharma, 2024)
Lack of financial literacy and supported by the ease of technology, as well as the YOLO (You Only Live Once) and FOMO (Fear of Missing Out) views that developed among Gen-Z, causing them to be less able to manage expenses. Therefore, it is necessary to improve financial literacy and strategies to achieve financial freedom for Gen-Z. The community service activity organized was in the form of a Webinar which was attended by Gen-Z employees aged 20-26 years. Webinar participants came from Trilogy University Employee class students and the general public. The results of the webinar showed an increased understanding of the importance of financial planning, the availability of sufficient emergency funds, and the strategies needed to prepare for the future through minimum savings and investments that must be made programmatically.Kurangnya literasi keuangan dan didukung oleh kemudahan teknologi, serta pandangan YOLO (You Only Live Once) dan FOMO (Fear of Missing Out) yang berkembang di kalangan Gen-Z, menyebabkan mereka kurang dapat mengatur pengeluaran. Sehingga perlu adanya peningkatan literasi keuangan serta strategi untuk mencapai kebebasan finansial bagi Gen-Z. Kegiatan pengabdian masyarakat yang diselenggarakan berbentuk Webinar yang diikuti oleh para karyawan Gen-Z yang berusia 20-26 tahun. Peserta webinar berasal dari mahasiswa kelas Karyawan Universitas Trilogi serta masyarakat umum. Hasil webinar menunjukkan adanya peningkatan pemahaman tentang pentingnya perencanaan keuangan, tersedianya dana darurat yang cukup, serta strategi yang dibutuhkan untuk mempersiapkan masa depan melalui tabungan minimal serta investasi yang harus dilakukan secara terprogram.